Student Politics in South Africa. An Overview of Key Developments - Gabriel Cele; Charlton Koen (Cahiers de la Recherche sur l'Education et les Savoirs, 2003)
This paper discusses the structure of South Africa’s racially divided higher education sector and shows its development since the establishment of the first post-secondary institution in 1829. It also traces the key organizational changes that characterize the development of national political black student structures and discusses student identity concerns. Finally, it describes important changes during the 1990s that provide insight into the current challenges student leader’s face. Principally, this suggests that student representative councils and national political organisations have changed from protest oriented structures to structures focusing on economic, rather than political issues.